2021
DOI: 10.31219/osf.io/cu4jz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The COVID States Project #71: Childhood COVID-19 vaccine uptake and intentions

Abstract: In early November 2021, children ages 5-11 were authorized by the Centers for Disease Control and Prevention (CDC) to receive the Pfizer-BioNTech COVID-19 vaccine, making an additional 28 million children eligible for the shot. Given this significant advancement in COVID-19 vaccine availability - particularly in light of recent concerns over the Omicron variant - in this report we examine parent-reported COVID-19 vaccination intentions and uptake for children.Below, we examine reported childhood vaccination ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Earlier studies showed lower COVID-19 vaccine confidence among Hispanic populations, but in our study, Hispanic parents reported higher COVID-19 vaccine acceptance for their children than non-Hispanic parents [ 24 , 35 ]. Our finding is consistent with more recent studies of COVID-19 vaccine acceptance and uptake among Hispanic populations [ 26 , 27 , 29 ]. These changes in attitudes may be due to targeted community outreach over the course of the pandemic and the cumulative burden of disease suffered by the Hispanic community [ 1 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies showed lower COVID-19 vaccine confidence among Hispanic populations, but in our study, Hispanic parents reported higher COVID-19 vaccine acceptance for their children than non-Hispanic parents [ 24 , 35 ]. Our finding is consistent with more recent studies of COVID-19 vaccine acceptance and uptake among Hispanic populations [ 26 , 27 , 29 ]. These changes in attitudes may be due to targeted community outreach over the course of the pandemic and the cumulative burden of disease suffered by the Hispanic community [ 1 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has found vaccinated parents much more likely than unvaccinated parents to be willing to vaccinate their children [8,[12][13][14][15][16][17][18][19][20][21][22]. Prior studies have also found likelihood of child vaccination higher among parents of older children, older parents, higher educated parents, Democrat-affiliated parents, insured parents, higher income parents, Hispanic and Asian parents, parents with routine influenza vaccine behavior, and male gender [12,13,15,21,22,31,32]. Unlike past research, we find lower income parents have higher odds for willingness on three of four multivariate models.…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in COVID-19 vaccination rates among 12–17 year-olds since FDA emergency authorization in May 2021, to date, 9.9 million or nearly half of U.S. adolescents remain unvaccinated ( 5 – 7 ) in comparison to 61–85% of U.S. adults depending on age group ( 33 ). As such, concerns about parental pediatric vaccine refusal are growing.…”
Section: Discussionmentioning
confidence: 99%
“…As of December 8, 2021, however, just 51% (~12.8 million) of 12–17 year-olds were fully vaccinated ( 5 ). With 9.9 million youth remaining unvaccinated, a slow-down in vaccine uptake has become a growing concern ( 5 – 7 ). Consequently, understanding factors contributing to COVID-19 vaccine uptake among this age group is urgent.…”
Section: Introductionmentioning
confidence: 99%